Implementasi Pembangunan Zona Integritas di Balai Besar Wilayah Sungai Brantas Kota Surabaya - Alvy Nova Sabilla; Indah Prabawati; Suci Megawati; Tjitjik Rahaju (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The integrity zone program is a work unit or government agency that has successfully encouraged the creation of good governance and has good public service standards. The Brantas River Basin Center of Surabaya City is a work unit that implements the integrity zone program and found problems related to complaints about the long time it takes to complete services due to the long bureaucratic process so that services have not run optimally. Meanwhile, from the policy implementer's side, there are obstacles related to difficulties in filling out evaluation worksheets and compiling supporting evidence according to the assessment provisions, which causes the integrity zone development process to not run optimally. This study uses a descriptive method with a qualitative approach. Data sources used are primary and secondary data. Data collection techniques include observation, interviews, and documentation. Data analysis techniques through data collection, data reduction, data presentation, and verification. The focus of this study uses the theory of George C. Edward III, namely communication, resources, disposition, and bureaucratic structure. The results of this study on the communication indicator still found obstacles in the dissemination of information received by the target group, namely field workers and the community. In the resource indicator, there were obstacles in the placement of cross-sector members and a suboptimal digital service system. In the position variable, there has been a commitment to program implementation. Indicators of bureaucratic structure have been implemented, the standard operating procedures have not been formed and coordination between teams is running well.